2017
DOI: 10.1186/s13195-017-0324-0
|View full text |Cite
|
Sign up to set email alerts
|

Oligomeric forms of amyloid-β protein in plasma as a potential blood-based biomarker for Alzheimer’s disease

Abstract: BackgroundSoluble amyloid-β (Aβ) oligomers are the major toxic substances associated with the pathology of Alzheimer’s disease (AD). The ability to measure Aβ oligomer levels in the blood would provide simple and minimally invasive tools for AD diagnostics. In the present study, the recently developed Multimer Detection System (MDS) for AD, a new enzyme-linked immunosorbent assay for measuring Aβ oligomers selectively, was used to detect Aβ oligomers in the plasma of patients with AD and healthy control indivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
109
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 121 publications
(119 citation statements)
references
References 32 publications
5
109
0
1
Order By: Relevance
“…A previous study confirmed that the plasma OAβ level increases in plasma of AD patients but does not increase in the plasma of healthy normal control [12]. The increase in the plasma AβO level in AD highly correlates with CSF Aβ42 and Pittsburgh compound B (PiB) PET standard uptake ratio [13]. In addition, the elevated plasma OAβ level showed a strong correlation with cognitive performance in patients with AD, including an inverse correlation with scores on the mini-mental status examination (MMSE), cognitive abilities screening instrument, the common objects memory test, and a positive correlation with the Alzheimer's disease assessment scale-cognitive portion scores [14].…”
Section: Introductionmentioning
confidence: 52%
“…A previous study confirmed that the plasma OAβ level increases in plasma of AD patients but does not increase in the plasma of healthy normal control [12]. The increase in the plasma AβO level in AD highly correlates with CSF Aβ42 and Pittsburgh compound B (PiB) PET standard uptake ratio [13]. In addition, the elevated plasma OAβ level showed a strong correlation with cognitive performance in patients with AD, including an inverse correlation with scores on the mini-mental status examination (MMSE), cognitive abilities screening instrument, the common objects memory test, and a positive correlation with the Alzheimer's disease assessment scale-cognitive portion scores [14].…”
Section: Introductionmentioning
confidence: 52%
“…Different technologies have been investigated and some have shown promise; examples include ELISA-based methods in CSF [143, 312, 396] and in plasma [381], single-molecule fluorescence microscopy in CSF [144], and a protein misfolding cyclic amplification assay method in CSF [308]. However, the overall findings have been inconsistent or unsatisfactory (reviewed by Schuster and Funke [318]).…”
Section: Aβ Pathologymentioning
confidence: 99%
“…A number of studies have suggested that plasma Ab42 and Ab40 measures, as well as the ratio of Ab42/ Ab40 are reduced in patients with AD and MCI and that these plasma biomarkers can predict the presence of AD and MCI and progression from normal to impaired cognition [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. However, other studies have shown that higher plasma Ab measures are associated with AD and conversion to AD [19][20][21][22][23][24]. Still, others have found no significant relationship [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…Reduced plasma Ab has also been linked to poorer cognition [6,7,19,21,[27][28][29][30]. In addition, some studies have suggested that plasma levels of Ab42 and Ab40 are associated with the levels of cerebral Ab on positron emission tomography (PET), cerebrospinal fluid levels of Ab and tau, and AD-like brain atrophy [4,7,8,11,16,17,24,[31][32][33][34][35][36][37][38], while others have not seen such an association [25,39,40]. These conflicting results may be due to the type of plasma markers measured and the methodologies used to extract these values.…”
Section: Introductionmentioning
confidence: 99%